Is Your Error My Concern? An Event-Related Potential Study on Own and Observed Error Detection in Cooperation and Competition - De Bruijn, Ellen R.; von Rhein, Daniel T. (Frontiers in Neuroscience, 2012)
For successful goal-directed behavior it is essential for humans to continuously monitor one’s actions and detect errors as fast as possible. EEG studies have identified an error-related ERP component known as the error-related negativity or ERN. Theories on error monitoring propose a direct relation to reward processing. Whenever an error is made, the outcome of an action turns out to be worse than expected, resulting in a loss of reward and hence eliciting the ERN. However, as own errors are always associated with a loss of reward, disentangling whether the ERN is error- or reward-dependent has proven to be an extremely difficult endeavor. Recently, an ERN has also been demonstrated following the observation of other’s errors. An important difference with own errors is that other people’s errors can be associated with loss or gain depending on the cooperative or competitive context in which they are made. We conducted an ERP study to disentangle whether performance monitoring is error- or reward-dependent. Twelve pairs (N=24) of participants performed and observed a speeded-choice reaction task in two contexts. Own errors were always associated with a loss of reward. Observed errors in the cooperative context also yielded a loss of reward, but observed errors in the competitive context resulted in a gain. The results showed that the ERN was present following all types of errors independent of who made the error and the outcome of the action. Consequently, the current study demonstrates that performance monitoring as reflected by the ERN is error-specific and not directly dependent on reward.